2014
DOI: 10.2174/0929867321666140601163244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron and Copper Overload on the Human Liver: An Ultrastructural Study

Abstract: Iron and copper ions play important roles in many physiological functions of our body, even though the exact mechanisms regulating their absorption, distribution and excretion are not fully understood. Metal-related human pathology may be observed in two different clinical settings: deficiency or overload. The overload in liver cells of both trace elements leads to multiple cellular lesions. Here we report the main pathological changes observed at transmission electron microscopy in the liver of subjects affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…A previous study reported the use of electron microscopy to demonstrate the presence of a large number of lipid droplets in the hepatocytes of an adult with CTLN2; however, this group evaluated an autopsied specimen . The presence of lipid droplets in hepatocytes, as demonstrated by electron microscopy, is not specific to citrin deficiency; however, this finding may be a clue for the diagnosis of citrin deficiency in the absence of fatty changes, as determined by light microscopy. Small vacuoles were observed within the hepatocytes in this patient.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study reported the use of electron microscopy to demonstrate the presence of a large number of lipid droplets in the hepatocytes of an adult with CTLN2; however, this group evaluated an autopsied specimen . The presence of lipid droplets in hepatocytes, as demonstrated by electron microscopy, is not specific to citrin deficiency; however, this finding may be a clue for the diagnosis of citrin deficiency in the absence of fatty changes, as determined by light microscopy. Small vacuoles were observed within the hepatocytes in this patient.…”
Section: Discussionmentioning
confidence: 93%
“…Despite this long-standing medical use of iron, iron deficiency continues to affect 30% of the world population, is the most severe and widespread nutritional deficiency disorder, and remains the only nutritional deficiency disorder in industrialized countries 4,5 . On the other hand, iron overload causes accumulation of iron in various tissues and can result in cirrhosis 6 , neurodegenerative and cardiovascular diseases (cardiomyopathy, etc.) 7,8 that result from formation of reactive oxygen species through Fenton or Haber−Weiss reactions 9 .…”
Section: Introductionmentioning
confidence: 99%
“…They form a variety of compounds with interesting spectroscopic and magnetic properties whose practical applications are the subject of ongoing research [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In the cell, metals are usually found in their complexed form, either as standalone ions or inside specific planar carrier compounds encapsulated by proteins -e.g.…”
Section: Metal Ions In Natural Biological Systemsmentioning
confidence: 99%